Finance, gender, and entrepreneurship: India's informal sector firms - Ira N. Gang; Rajesh Raj Natarajan; Kunal Sen (Global Labor Organization (GLO), 2020)
How does informal economic activity respond to increased financial inclusion? Does it become more entrepreneurial? Does access to new financing options change the gender configuration of informal economic activity and, if so, in what ways and what directions? We take advantage of nationwide data collected in 2010/11 and 2015/16 by India's National Sample Survey Office on unorganized (informal) enterprises. This period was one of rapid expansion of banking availability aimed particularly at the unbanked, under-banked, and women. We find strong empirical evidence supporting the crucial role of financial access in promoting entrepreneurship among informal sector firms in India. Our results are robust to alternative specifications and alternative measures of financial constraints using an approach combining propensity score matching and difference-in-differences. However, we do not find conclusive evidence that increased financial inclusion leads to a higher likelihood of women becoming entrepreneurs than men in the informal sector.
Keywords: O12; G28; L26; 330; entrepreneurship; financial constraints; gender; informal sector; difference-indifferences; India